Audiovisual Programs for Promoting a SDG Culture: Rethinking the 2030 Agenda on Culture, Art and Communication in Brazilian Universities - Cabral, Raquel [UNESP]; P. Xavier, Juarez T. [UNESP]; Ferreira, Mayra [UNESP]; dos S. Feltrin, Diuan [UNESP] (Springer Nature, 2024)
This chapter presents the results of inter-institutional partnerships based on principles of communication for peace, reflecting on the Epistemologies of the South and the convergence between the Sustainable Development Goals (SDGs) of the UN 2030 Agenda and science. Based on critical reflections and experiences from the following three Brazilian universities, São Paulo State University (Unesp), The Federal University for Latin American Integration (UNILA), and the University of Brasilia (UnB), we noted that the communicative process met the fundamental communication guidelines for promoting the culture of the SDGs, such as (1) a commitment to discuss issues related to the various forms of violence in society; (2) produce narratives that deconstruct colonial points of view; (3) promote a diversity of narratives for the different social groups involved in and affected by logics that legitimize violence; and (4) promote democratic access to scientific knowledge through communication for science. Based on these concrete experiences, we analyze the pertinence of the communicational dimension of the 2030 Agenda, which reiterates the importance of a specific SDG which focuses on Culture, Art, and Communication.
Keywords: 2030 Agenda; Communication for peace; Democratization of science; Global South knowledge; SDG